The impact of sustainability practices on firm financial performance: evidence from Malaysia / Christopher Jerry Thomas ...[et al.] - Thomas, Christopher Jerry; Tuyon, Jasman; Matahir, Hylmee; Dixit, Samir (UiTM Press, 2021)
In line with the United Nations (UN) sustainable development agenda, corporate sustainability is a critical driver for a corporation’s long-term survival. Despite the noble ideas, sustainability practices remain neglected in theory, policy, and selectively practiced by Malaysian corporations, possibly due to unclear impacts. This study aimed to provide an empirical analysis on the impact of sustainability practices on firm performance in the context of Malaysia using both aggregate and disaggregated environmental, social and governance (ESG). The study sample consisted of 36 public listed firms in Malaysia that have been consistently reporting ESG scores from 2015 to 2019. Static panel regression was used to analyse the data in annual frequency. In aggregate level, the results indicated a positive relationship between sustainability (ESG) and firm financial performance such as, return on assets (ROA), return on equity (ROE) and Tobin’s Q (TQ), but only significant for ROE. In disaggregate, the result revealed that there is a significant positive relationship between S score with (ROE and TQ) and G score with TQ. Theoretically, sustainable finance and stakeholder engagement promote profitable growth in equity returns which enhance corporate performance. Policymakers, regulators, and governments should improve regulatory frameworks to ensure good ESG transparency in enhancing firm value.